2019
DOI: 10.3390/electronics8091011
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Occupancy Measurements and Analysis in 2.4 GHz WLAN

Abstract: High time resolution spectrum occupancy measurements and analysis are presented for 2.4 GHz WLAN signals. A custom-designed wideband sensing engine records the received power of signals, and its performance is presented to select the decision threshold required to define the channel state (busy/idle). Two sets of measurements are presented where data were collected using an omni-directional and directional antenna in an indoor environment. Statistics of the idle time windows in the 2.4 GHz WLAN are analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…LTE based), they can provide an initiative for a UAV enabled 3D channel models [93,94]. Furthermore, the placement of UAV BS for effective energy utilization with maximum coverage [95] while also taking into account the overall network delay [96], interference management from adjacent cells [97,98], dynamic spectrum access for UAV enabled networks [99], and 3D positing control [100] are vital research areas for UAV enabled network and required further investigation.…”
Section: Uav Based Heterogeneous 3d Wireless Networkmentioning
confidence: 99%
“…LTE based), they can provide an initiative for a UAV enabled 3D channel models [93,94]. Furthermore, the placement of UAV BS for effective energy utilization with maximum coverage [95] while also taking into account the overall network delay [96], interference management from adjacent cells [97,98], dynamic spectrum access for UAV enabled networks [99], and 3D positing control [100] are vital research areas for UAV enabled network and required further investigation.…”
Section: Uav Based Heterogeneous 3d Wireless Networkmentioning
confidence: 99%
“…In [19] exploits the unused spectrum and determines the maximum permitted transmitting power on the basis of the radio environment maps. In addition, high time resolution spectrum occupancy measurements and analysis are presented in [2] for 2.4 GHz WLAN signals. The authors propose a custom-designed wideband sensing engine to record the received power of signals, and its performance is presented to select the decision threshold required to define the channel state (busy/idle).…”
Section: Related Workmentioning
confidence: 99%
“…On the basis of the Intel Core i7-8750H processor and RTX 2060 graphics card, the PRF and PRF-NFE need 6.7 s and 2.5 s per iteration, respectively. We prefer the PRF algorithm for 3 reasons: (1) the PRF algorithm has a better estimation performance than PRF-NFE, as verified by the following subsection; (2) The training data are limited in most cases. As for the REMs estimation task, a neural network with stronger information extracting ability is important because of the limited and incomplete training images; (3) A computer with a more powerful calculation ability can solve the time-consuming problem for the training process of the PRF algorithm.…”
Section: Settings Of the Prf Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheema and Salous [6] have conducted various high time resolution spectrum occupancy measurements and analysis for 2.4 GHz WLAN signals. To this end, it was found that distributions such as Gamma and lognormal can be used to model the idle state of a 2.4 GHz WLAN channel along with the generalized Pareto distribution.…”
mentioning
confidence: 99%